2020
DOI: 10.1017/s1041610220003397
|View full text |Cite
|
Sign up to set email alerts
|

Fear about Alzheimer’s disease among Israeli and German laypersons, persons with Mild Neurocognitive Disorder and their relatives: a qualitative study

Abstract: Objectives: Alzheimer’s disease (AD), the most common type of dementia, is one of the most feared diseases, obstructing help-seeking, and leading to discrimination. While research interest in fear of developing AD is increasing, little is known about its characterization, triggers, and consequences, especially among different cultures. In this study, we aimed at exploring and characterizing AD fear as experienced by laypersons (LP), persons with Mild Neurocognitive Disorder (MND), and their relatives, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(72 reference statements)
2
11
0
Order By: Relevance
“…Participants in this study described experiences and views suggesting a lack of community awareness about the lived experiences of dementia, and/or a disconnection between awareness, and compassionate and empathetic responses toward people living with dementia. These findings complement those of a qualitative study of people with mild neurocognitive disorder in Israel and Germany (Werner et al, 2021) whose overarching themes included fear of developing Alzheimer's disease and fear of stigmatization. Themes in that study specific to people living with dementia and their families indicated that different types of fear match different reasons such as fear of the impact of a diagnosis on family members, fear of becoming a caregiver, and fear of losing selfdetermination because of dementia (Werner et al, 2021).…”
Section: Stigma and Discriminationsupporting
confidence: 69%
See 1 more Smart Citation
“…Participants in this study described experiences and views suggesting a lack of community awareness about the lived experiences of dementia, and/or a disconnection between awareness, and compassionate and empathetic responses toward people living with dementia. These findings complement those of a qualitative study of people with mild neurocognitive disorder in Israel and Germany (Werner et al, 2021) whose overarching themes included fear of developing Alzheimer's disease and fear of stigmatization. Themes in that study specific to people living with dementia and their families indicated that different types of fear match different reasons such as fear of the impact of a diagnosis on family members, fear of becoming a caregiver, and fear of losing selfdetermination because of dementia (Werner et al, 2021).…”
Section: Stigma and Discriminationsupporting
confidence: 69%
“…These findings complement those of a qualitative study of people with mild neurocognitive disorder in Israel and Germany (Werner et al, 2021) whose overarching themes included fear of developing Alzheimer's disease and fear of stigmatization. Themes in that study specific to people living with dementia and their families indicated that different types of fear match different reasons such as fear of the impact of a diagnosis on family members, fear of becoming a caregiver, and fear of losing selfdetermination because of dementia (Werner et al, 2021). Fear of stigmatization arising from a dementia diagnosis led our study participants to use different coping strategies depending on the emotion/ behavior they experienced.…”
Section: Stigma and Discriminationsupporting
confidence: 69%
“…The current study showed that increased ageism and an increased level of the perceived risk of developing dementia were the most important factors associated with dementia worry. These results have potentially useful implications as both can be manipulated to decrease their level or to direct their influence toward positive behaviors, such as engaging in preventive behaviors [ 8 ]. The association between perceived risk and worry is not surprising, as they reflect the cognitive and affective components of a threat, as has been found in the area of cancer worry [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to the best of our knowledge, to date, only one study has explored and characterized dementia worry cross-culturally. The results of this qualitative study—based on a sample of 130 laypeople comprising people with mild neurocognitive disorder and their relatives in Israel and Germany—revealed similarities as well as differences in the meaning attributed to dementia worry and in its triggering and coping mechanisms across cultures [ 8 ]. The findings of this pioneering study stress the importance of extending research in the area of dementia worry and culture, especially among non-affected people.…”
Section: Introductionmentioning
confidence: 99%
“…It is for this reason that this new paper (Werner et al, 2020) titled: "Fear about Alzheimer's disease among Israeli and German laypersons, persons with Mild Neurocognitive Disorder and their relatives: A qualitative study" makes a welcome contribution to the dementia care literature. The paper is based on a cross-national comparative study, designed to address the question: What are the main perceptions and experiences of "dementia fear" among different groups of people?…”
mentioning
confidence: 99%